Evaluasi mutu dodol dengan penambahan rumput laut cokelat (Sargassum sp.) sebagai makanan olahan sehat - Indira Karina; Desrizal (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Dodol is an ingredient of traditional food which is already known by the Indonesian people, because it is tasty and the high nutritional content. One of a combination of refined products healthy with dodol in supporting the fulfillment of food and nutrition is seaweed, therefore the processing dodol with the addition of seaweed can be categorized as a product of processed food which is healthy and safe to be consumed by the consumer. The purpose of this research was to know the quality of dodol with the addition of brown seaweed through organoleptic/ teshedonic test (taste, color, and aroma) and proximate test (water content and ash content). The method used in this research was experimental method that was doing the experiment of making dodol by adding seaweed. Furthermore, the organoleptic test and proximate test are done. The research design used in this study was Completely Randomized Design (RAL) with 5 treatments and 3 replications. The data obtained were analyzed statistically with F test and Duncan's New Multiple Range Test (DNMRT) advanced test at 5% real level. The results showed the lowest water content found in treatment E (addition of 50% brown seaweed). The results of organoleptic assessment, dodol with the addition of brown seaweed most favored by panelists in terms of taste, color, and aroma is the C treatment (addition of 30% brown seaweed). The quality of Dodol rumput laut coklat most liked is with the addition of brown seaweed by 30%. The addition of brown seaweed can be a solution in improving the nutritional value and quality on the food like on the dodol also can reduce the water content in the dodol.